Configuration of the Emergency Room at Toto Kabila Regional Hospital Based on Space Syntax Analysis - Rahmat Firdaus Bouty (Architectural Research Journal, 2024)
A hospital is a health service institution that functions for health services. In the composition of the units in the hospital there are several installations, one of which is the emergency department. Emergency Room (ER) services are very important because they are the main door to hospital services, so they require accessibility and visibility which makes it easier for medical personnel to treat patients. The importance of ease of access or accessibility in the ER is because it makes it easier for medical staff to review patients and ease of monitoring or visibility is needed to be able to control the patient's condition. The ease of accessibility and visibility in the emergency room unit is the basis for this research by assessing the configuration of the emergency room at Toto Kabila Regional Hospital. This research uses Depthmap X software from the Space Syntax technique which can measure the level of spatial configuration from the analysis carried out. The research method used is comparative research, where this research was carried out by comparing the results of the analysis of the speed performance relationship in the emergency room using the Space Syntax tool in the emergency room at Toto Kabila Regional Hospital. This research aims to explain the space configuration in the emergency room at Toto Kabila Regional Hospital by conducting an analysis so that it has criteria for ease of achievement and ease of supervision in order to produce a good emergency room through the use of depthmap software from space syntax. The research results show that accessibility and visibility are important so that patients receive fast service.